2022
DOI: 10.3389/fgene.2022.818940
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Microbial Community Diversity and Dynamics on Diseased Tubers During Potato Storage in Different Regions of Qinghai China

Abstract: Effective storage of potatoes is very important for the food industry. Given the problems involving rotten potatoes and low quality during storage, harvested potatoes from the main potato-producing areas in the Qinghai Plateau were treated by selection and air drying (Group “A”) and the others were stored directly as controls (Group “C”). Then, the microbial community structure and diversity of diseased potato tubers from four main production areas were analyzed by high-throughput sequencing technology in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
(73 reference statements)
1
2
0
Order By: Relevance
“…Kusstatscher et al (2019) found an increase in saprophytic fungi in healthy samples. The function of plant pathogens in the roots of diseased plants was obviously higher than that of healthy plants, which is consistent with the research results of Xie et al (2022).…”
Section: The Pathogen Presence Correlates With Changes In the Diversi...supporting
confidence: 90%
“…Kusstatscher et al (2019) found an increase in saprophytic fungi in healthy samples. The function of plant pathogens in the roots of diseased plants was obviously higher than that of healthy plants, which is consistent with the research results of Xie et al (2022).…”
Section: The Pathogen Presence Correlates With Changes In the Diversi...supporting
confidence: 90%
“…Fusarium, Alternaria, and Colletotrichum are the main fungal pathogens of potatoes in storage. In this regard, Ascomycota was reported to be the dominant fungal phylum in symptomatic and asymptomatic groups of potato tubers during storage 24 . Fusarium was also the most abundant fungal genus in stored oat seeds.…”
Section: Discussionmentioning
confidence: 99%
“…The Venn diagrams showed that changes in temperature and humidity did not significantly affect the relevant core species, and the differences in temperature and humidity were influential in only a smaller range of species. A variety of fungal species were obtained by sequencing, but most fungi would not grow and reproduce; only a few core microorganisms were still developing ( Xie et al, 2022 ). Under some special external environmental conditions, the dominant genus will change and have adverse effects ( De Filippis et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%